Long-term changes in soil aggregation comparing forest and agricultural land use in different Mediterranean soil types - Chrenková, Katarína; Mataix-Solera, Jorge; Dlapa, Pavel; Arcenegui, Victoria (Geoderma, 2014)
The formation and stabilization of soil aggregates have a key role to play in adequate soil functioning. Aggregate stability (AS) is considered by some authors to be a property that provides information on soil quality. It's also a property that is highly influenced by land use and management. This study aims to identify the long-term changes in soil aggregation and related properties comparing forest and agricultural land use in Mediterranean calcareous soils. For the research, seven study sites with different soil characteristics located in Alicante Province (E Spain) were chosen to compare the overall effect of land use change from agriculture to forestry on soil aggregation. At every site, samples of the same soil type were collected from agricultural land (dry crops with conventional tillage management using ploughing), and nearby forest, where agriculture was abandoned between 20 and 50years ago. Selected physical and chemical properties like: texture, total content of aggregates (TCA), aggregate stability (AS), organic matter content (OM), carbonates, mean weight diameter (MWD) of aggregates and water repellency (WR) were analysed on the collected soil samples. As expected, in all soils, the AS was significantly lower in agricultural sites than in forest sites. But in some cases the differences were much higher than in others. In forest sites the AS varied between 46 and 82% while in agricultural sites it ranged between 14 and 45%. The results showed strong positive correlation of AS with OM. The lowest values of AS in forest areas were found in wettable sandy soils. The relative increase of AS in forest soils compared to agricultural land use ranged from 39 to 79%. These differences can be explained mainly by some soil properties, such as OM content, texture, and WR. In particular, the lower OM content and absence of WR are responsible for the lower values of AS in agricultural land use due to the long-term conventional tillage management. Soil WR was found in three of the sites, and its presence plays a key role in soil aggregation and its stability, especially for sandy soils. The MWD was in most cases higher in forest than in agricultural sites, except for two wettable sandy soils with the lowest initial AS. In the case of carbonates, no correlations were found with AS, and only in the group of sandy soils, significant positive correlations between carbonates and TCA and with MWD were found. In conclusion we can say that the prolonged use of conventional tillage management using ploughing has a strong influence on AS in all types of soils studied in this research. The recovery after decades of land use abandonment not only is dependent on how is the increase of soil OM content, but also is controlled by some soil properties such as the texture and the presence of WR. In some cases the presence of hydrophobic substances can play a key role in the formation and stabilization of soil aggregates, contributing to maintaining good levels of OM and avoiding higher levels of soil degradation.
Keywords: Aggregate stability; Conventional tillage; Mean weight diameter; water repellency

Soil aggregate stability under different Mediterranean vegetation types - Cerdá, A (Catena, 1998)
The influence of vegetation type on soil erodibility was studied by means of aggregate stability measurements using the Modified Emerson Water Dispersion Test MEWDT , water-drop impacts . . . CND and TDI and Ultrasonic Disruption UD methods on soils from north-facing slopes of the mountain range of La Serra Grossa in the eastern Iberian Peninsula. Soils with similar characteristics but covered by the main plant species at the study area were selected. Quercus ilex woodland showed the most resistant soil aggregates followed by Q. coccifera and Pistacea lentiscus scrubland, Brachypodium retusum grassland and Pinus halepensis woodland. Aggregates developed beneath dwarf shrubs like Rosmarinus officinalis, Thymus Íulgaris, Ulex parÍiflorus and Anthyllis cystisoides were least resistant. The different methods and tests applied are useful to study the soil aggregate stability. The MEWDT and TDI tests showed only minor differences between samples due to the high aggregate resistance and the low energy applied by these tests. CND and UD tests are considered to be more suitable for resistant Mediterranean soil developed on limestone due to the greater energy applied. Aggregates tested from an initially moist pF1 condition were always more stable than air dried aggregates. Rangeland management . after disturbances by fire, agriculture or grazing, etc. should try to establish natural woodland Q. ilex. in order to get the most stable soil. Alternative vegetation cover to the climax vegetation that give high aggregate stability are Q. coccifera and P. lentiscus scrublands. Immediately after disturbance, B. retusum grassland seems to be the best option for soil protection.
Keywords: Aggregate stability; Laboratory test; Mediterranean; Vegetation

Soil aggregate stability under different Mediterranean vegetation types - Cerdà, A. (Catena, 1998)
The influence of vegetation type on soil erodibility was studied by means of aggregate stability measurements using the Modified Emerson Water Dispersion Test MEWDT , water-drop impacts . . . CND and TDI and Ultrasonic Disruption UD methods on soils from north-facing slopes of the mountain range of La Serra Grossa in the eastern Iberian Peninsula. Soils with similar characteristics but covered by the main plant species at the study area were selected. Quercus ilex woodland showed the most resistant soil aggregates followed by Q. coccifera and Pistacea lentiscus scrubland, Brachypodium retusum grassland and Pinus halepensis woodland. Aggregates developed beneath dwarf shrubs like Rosmarinus officinalis, Thymus Íulgaris, Ulex parÍiflorus and Anthyllis cystisoides were least resistant. The different methods and tests applied are useful to study the soil aggregate stability. The MEWDT and TDI tests showed only minor differences between samples due to the high aggregate resistance and the low energy applied by these tests. CND and UD tests are considered to be more suitable for resistant Mediterranean soil developed on limestone due to the greater energy applied. Aggregates tested from an initially moist pF1 condition were always more stable than air dried aggregates. Rangeland management . after disturbances by fire, agriculture or grazing, etc. should try to establish natural woodland Q. ilex. in order to get the most stable soil. Alternative vegetation cover to the climax vegetation that give high aggregate stability are Q. coccifera and P. lentiscus scrublands. Immediately after disturbance, B. retusum grassland seems to be the best option for soil protection.
Keywords: Aggregate stability; Laboratory test; Mediterranean; Vegetation